Project-Based Learning: A Case for Situated Translation - Kiraly, Don (Meta)

(untitled) (Les Presses de l'Université de Montréal, 2005)
AbstractThe author proposes replacing the folk theoretical ‘conduit’ view of learning that still predominates in Translator Education with a principled understanding of cognitive and learning processes for the design of learning events in Translator Education. A collaborative, project-based educational experience is presented by way of illustration. In conclusion, an argument is made for studying collaborative learning events to gain insight into the multi-facetted nature of the learning process as well as of the translation process itself.